Differentiated Profiles of Elected Officials in Montreal: A Specific Party Identity Around Mobility, Urban Planning, and Environment? - Breux, Sandra; Van Neste, Sophie L. (Frontiers in Political Science, 2022)
In Quebec, in 2004, a new municipal political party was created in Montreal: the Projet Montréal party. Several aspects distinguish this party from other municipal political parties. Among these—the supposedly particular composition of the party's team and its activists, which brings together academics, environmental activists and experts in urban planning and transportation—attracts attention. The objective of this paper is to verify the specificity of the profiles of elected officials of the Projet Montréal political party by comparing them with those of other elected officials affiliated with municipal political parties between 2009 and 2017. Based on an extensive documentary survey of the 103 elected officials of the City of Montréal during the last three municipal elections, we will present how the profiles of elected officials differed depending on whether or not they belonged to Projet Montréal. More specifically, we will show that the profiles of Projet Montréal officials are more pronounced in the area of “mobility, urban planning, and environment” understood as one broad entity, whereas those of the other parties are stronger in the fields of administration and commerce. That said, the characteristics of the Projet Montréal team did shift over the course of the elections, insofar as officials with an education in the respective mentioned fields have made way for participants with more of an activist and volunteer profile. This research thus offers a first different and longitudinal look at the evolution of a municipal political party, the project it carries and the way in which the elected officials who compose it contribute to the identity of the party. By doing so, this study also shed light on municipal democracy and the conditions of entry into political office in that context.